2000
DOI: 10.1128/jb.182.15.4227-4233.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Alternative Nucleoside Triphosphate: 5′-Deoxyadenosylcobinamide Phosphate Nucleotidyltransferase inMethanobacterium thermoautotrophicumΔH

Abstract: Computer analysis of the archaeal genome databases failed to identify orthologues of all of the bacterial cobamide biosynthetic enzymes. Of particular interest was the lack of an orthologue of the bifunctional nucleoside triphosphate (NTP):5-deoxyadenosylcobinamide kinase/GTP:adenosylcobinamide-phosphate guanylyltransferase enzyme (CobU in Salmonella enterica). This paper reports the identification of an archaeal gene encoding a new nucleotidyltransferase, which is proposed to be the nonorthologous replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…Other New Members of the B 12 Regulon Related to the CBL Biosynthesis-The 1,2-propanediol utilization operon pdu of S. typhimurium includes the pduX gene of unknown function (44). Here we found that some Gram-positive bacteria, namely three clostridia, L. monocytogenes, D. halfniense, and H. mobilis, contain the pduX genes located within the CBL gene clusters, usually adjacent to the cobD gene (Table I).…”
Section: Table 1 Cobalamin Biosynthesis and Transport Genes And B12-ementioning
confidence: 70%
“…Other New Members of the B 12 Regulon Related to the CBL Biosynthesis-The 1,2-propanediol utilization operon pdu of S. typhimurium includes the pduX gene of unknown function (44). Here we found that some Gram-positive bacteria, namely three clostridia, L. monocytogenes, D. halfniense, and H. mobilis, contain the pduX genes located within the CBL gene clusters, usually adjacent to the cobD gene (Table I).…”
Section: Table 1 Cobalamin Biosynthesis and Transport Genes And B12-ementioning
confidence: 70%
“…Therefore, the addition of acetate to minimal medium might reduce the total cobamide demand and allow for growth on reduced concentrations of cobamide. To verify this hypothesis, the concentrations of cobamides in extracts of wild type and JJ117 were determined with the indicator strain S. enterica serovar Typhimurium TR6583 (Maggio-Hall and Escalante-Semerena 1999, Thomas and Escalante-Semerena 2000). Detectible but low amounts of cobamides were found in extracts of the mutant JJ117 (Figure 6A).…”
Section: Quantification Of Cobamide In the Wild Type And Jj117mentioning
confidence: 96%
“…Of this, 4 ml was concentrated to dryness in a high speed vac (Uniequip, Martinsried, Germany) and resuspended in 50 µl of distilled water. The cobamide concentration was estimated as described by Maggio-Hall and Escalante-Semerena (1999) and Thomas and Escalante-Semerena (2000). For this experiment, Vogel-Bonner medium overlaid by 3 ml of medium containing Salmonella enterica serovar Typhimurium TR6583 [metE205 ara-9] or JE1299 [metE205 ara-9 btuB7::MudJ] were spotted with 2.5 or 5 µl of various dilutions of the methanococcal extracts.…”
Section: Measurement Of Cobamide Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvaging of Cby requires first its conversion to adenosylcobyric acid (AdoCby) by the ATP : co(I)rrinoid adenosylransferase (CobA) enzyme, followed by its conversion to adenosylcobinamide-phosphate (AdoCbi-P) by the Cbi-P synthase (CbiB) enzyme (Brushaber et al, 1998;Thomas & Escalante-Semerena, 2000). In contrast to Cby, Cbi is directly phosphorylated by CobU, the bifunctional kinase/guanylyltransferase enzyme whose kinase activity is dedicated to Cbi salvaging (Thomas & Escalante-Semerena, 2000). The lower ligand base in the structure shown in Fig.…”
Section: Introductionmentioning
confidence: 99%